Evaluation of Bone Graft (Hydroxyapatite + Platelet-Rich Plasma) Alone and in Combination with Diode Laser in Management of Infrabony Defect - Soumyadev Satpathy; Jyothi Gupta; Pavan Tenglikar; Rosaish Kanapathy; Dipanshu Shah; Anuj Singh Parihar; Vardharajula Venkata Ramaiah (Wolters Kluwer Medknow Publications, 2023)
Objective: The current study looked at how well bone graft (hydroxyapatite + platelet-rich plasma (PRP)) and a diode laser treated infrabony defects. Materials and Method: Twenty patients with bilateral infrabony deficiency were treated in a split-moth evaluation with bone graft (hydroxyapatite + PRP) alone (group I) (control) and bone graft combined with a diode laser (group II) (test). Clinical and radiologic measures such as the relative clinical attachment level (RCAL), probing depth (PD), gingival index (GI), and plaque index (PI) were recorded at baseline, 3 months later, and 6 months later in all patients. Result: At the 6-month follow-up, there was a decline in the plaque index, probing depth, gingival index, and relative clinical attachment level. Conclusion: When compared across groups, the intrabony pocket was significantly reduced with either the bone graft (hydroxyapatite + PRP) or in conjunction with the laser.